2022
DOI: 10.3390/jcm11236898
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Pharmacodynamics, and Dosing Considerations of Novel β-Lactams and β-Lactam/β-Lactamase Inhibitors in Critically Ill Adult Patients: Focus on Obesity, Augmented Renal Clearance, Renal Replacement Therapies, and Extracorporeal Membrane Oxygenation

Abstract: Objective: Dose optimization of novel β-lactam antibiotics (NBLA) has become necessary given the increased prevalence of multidrug-resistant infections in intensive care units coupled with the limited number of available treatment options. Unfortunately, recommended dose regimens of NBLA based on PK/PD indices are not well-defined for critically ill patients presenting with special situations (i.e., obesity, extracorporeal membrane oxygenation (ECMO), augmented renal clearance (ARC), and renal replacement ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 100 publications
(127 reference statements)
1
12
0
Order By: Relevance
“…Recently, Backdach et al [ 51 ] systematically reviewed the results of 27 articles on PK/PD characteristics of novel β-lactams and β-lactams/β-lactamase inhibitors in critically ill patients receiving ECOS. Specifically, they found that increasing doses of Cefiderocol (standard dose: 2 g Q8h) might be necessary to attain PK/PD indexes in relationship with residual renal function, highly resistant pathogen and CRRT intensity (from 1.5 g Q12h for effluent flow rate ≤ 2 L/h to 2 g Q8h for effluent flow rate ≥ 4 L/h), while the maintenance dose of Ceftolozane/Tazobactam should be lowered (from 1.5–3 g Q8h to 0.75 Q8h) during CRRT.…”
Section: Renal Replacement Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Backdach et al [ 51 ] systematically reviewed the results of 27 articles on PK/PD characteristics of novel β-lactams and β-lactams/β-lactamase inhibitors in critically ill patients receiving ECOS. Specifically, they found that increasing doses of Cefiderocol (standard dose: 2 g Q8h) might be necessary to attain PK/PD indexes in relationship with residual renal function, highly resistant pathogen and CRRT intensity (from 1.5 g Q12h for effluent flow rate ≤ 2 L/h to 2 g Q8h for effluent flow rate ≥ 4 L/h), while the maintenance dose of Ceftolozane/Tazobactam should be lowered (from 1.5–3 g Q8h to 0.75 Q8h) during CRRT.…”
Section: Renal Replacement Therapymentioning
confidence: 99%
“…Specifically, they found that increasing doses of Cefiderocol (standard dose: 2 g Q8h) might be necessary to attain PK/PD indexes in relationship with residual renal function, highly resistant pathogen and CRRT intensity (from 1.5 g Q12h for effluent flow rate ≤ 2 L/h to 2 g Q8h for effluent flow rate ≥ 4 L/h), while the maintenance dose of Ceftolozane/Tazobactam should be lowered (from 1.5–3 g Q8h to 0.75 Q8h) during CRRT. In contrast, no evidence was available for other antimicrobials such as Caftazidime/Avibactam, Imipenem/Relabatam and Meropenem/Vaborbactam [ 51 ].…”
Section: Renal Replacement Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Dose reduction for all, for example, following the commencement of renal replacement therapy, may result in suboptimal therapeutic levels for many patients [ 22 ]. On the contrary, total daily dosing must increase whenever there is augmented renal clearance of the administered antimicrobials [ 23 , 24 , 25 ]. All the drugs covered in this review, except for eravacycline and omadacycline, are hydrophilic, present a low volume of distribution and protein binding, and are renally cleared [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the process of choosing a PD metric for PTA analysis may lead to drastically different dosing conclusions based on the chosen target [ 7 ]. Furthermore, there are other less commonly used metrics, such as a cumulative fraction of response (CFR), which aid in the decision of which population subgroups to simulate, and other factors such as protein binding, which may also play a significant role in how dosing decisions are made [ 8 , 12 ]. The technical aspects of how the Monte Carlo simulations were performed may also have an impact on PTA [ 13 ].…”
Section: Introductionmentioning
confidence: 99%